A Teacher Action Research Study of the Potential for Communicative Learning Activities to Improve the Listening and Speaking Proficiency of Primary Students at a Private School in Thailand. - Fisher, David W. (2021)
Reports of the implementation of Communicative Language Teaching (CLT) in Thailand suggest that its success has been hampered by the key constraints of teacher-centredness, passive learning practices, national assessment requirements and student behaviours socially-prescribed by the dominant religion of Theravada Buddhism. This action research study seeks to measure the success of a set of communicative activities designed to promote listening and speaking proficiency, implemented in a primary class at a private school in northern Thailand. Evaluation of the outcomes involved video, interview and journal data collected from the students, teaching assistant and researcher. The results showed that students demonstrated the most successful learning through communicative activities that harnessed the potential of a teacher’s talk to actively engage students, included a competitive element that promoted student interaction, and provided opportunities for students to use language meaningfully. The research serves to confirm the findings of studies in multiple contexts that emphasise the importance of meaning-oriented activities to successful language teaching and learning, and refute the suggestion that educational culture in Thailand necessarily incapacitates students from being able to learn English communicatively.